A Beliefs Faith Local Products and Spiritual Tourism - Jomyim, Thanida (Journal of Modern business administration and management for Sustainable Development, 2024)
This academic article objective to study the concepts and theories of spiritual tourism, which is a form of travel associated with the search for the meaning of life and self-discovery. The development of spiritual tourism, including beliefs and faith, is crucial in creating identity and sustainable tourism. Spiritual tourism activities often involve religious and local belief-based activities. Additionally, promoting local products or sacred items to tourists who have beliefs and desires for spiritual enrichment can enhance the income of communities or localities. This process also fosters understanding and respect for religious and cultural diversity. Community involvement in various activities with sustainable tourists is another aspect, aligning with Thailand's spiritual tourism direction. This development has the potential to strengthen relationships between communities and both Thai and international tourists, making them the future destination for tourism.